Determinants of prices increase of agricultural commodities in a global context = Determinanty wzrostu cen surowców rolnych w warunkach globalnych - Borychowski, Michał; Czyżewski, Andrzej (Zielona Góra: Faculty of Economics and Management Press)
The main objective of this article is to present the determinants of increase in agricultural commodity prices after 2006. The other specific aim is to show the factors affecting agricultural raw materials and food prices in the global context. This article is a review paper of the determinants of recent commodity and food prices spikes. However, it provides an outlook on these determinants that were the most important for the increases in the last decade.
Keywords: surowce rolne; determinanty wzrostu cen; wzrost cen; relacje podażowo-popytowe; deprecjacja dolara; rynek rolny; polityka handlowa; agricultural raw materials; agricultural commodities; determinants of increase prices; supply-demand relations; dollar depreciation; agricultural markets; trade policy